Efficiency of Ð¡ombined Use of Cryopreserved Human Placenta Tissue and Calcium Citrate on Metabolism in Bone Tissue of Rats with Mandible Fracture on Background of Osteoporosis - Likhitskyi, Oleksii O. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 177